IT CONSISTS OF STUDYING THE ORIGIN, BOTANICAL, AND AGROBIOLOGICAL CHARACTERISTICS OF VARIETIES OF THE SUGAR SORGHUM (SACCHARATUM) PLANT (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2025)
The article studies the botanical and agrobiological characteristics, growth phases, and yield indicators of the sugar sorghum (Sorgum saccharatum) plant under local conditions.